Persepsi Mahasiswa PG-PAUD Universitas Muhammadiyah Ponorogo terhadap PAUD di Kabupaten Ponorogo, - M Fadlillah (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
The purpose of this study were (1) to know the perception of PGPAUD students toward early childhood education in Ponorogo District. (2) to know the obstacles of early childhood education in Ponorogo Regency based on perception of PG-PAUD students Muhammadiyah University of Ponorogo. The method used in this research is qualitative descriptive involving 30 students. Data collection was done by interview technique. The interview was conducted directly to the students of PGPAUD Muhammadiyah University of Ponorogo. The results of this study are 1) PGPAUD student perception on the implementation of early childhood education in Ponorogo regency in general has not run well according to national standards of early childhood education. 2) the obstacles of early childhood education in Ponorogo District are a) there are some teachers of PAUD who have not S1 PGPAUD, the welfare of early childhood teachers are still low, facilities and infrastructure is not adequate, and mininya assistance from the government, both central and local.